Application of whole exome sequencing in carrier screening for high-risk families without probands - Huang, Qinlin; Wang, Zhongjie; Teng, Yanling; Zhang, Wen; Wen, Juan; Zhu, Huimin; Liang, Desheng; Wu, Lingqian; Li, Zhuo (Frontiers in Genetics, 2024)
This study aimed to screen the genetic etiology for the high-risk families including those with an adverse pregnancy history, a history of consanguineous marriages, or a history of genetic diseases, but lack of proband via whole exome sequencing (WES).Methods: 128 individuals from high-risk family were tested by WES. The candidate variants were analyzed according to the ACMG criteria to screen the potential carriers. At-risk couples (ARCs) who harbored the same causative gene were provided with precise fertility guidance to avoid the birth of children with birth defects.The total detection rate was 36.72 %, with pathogenic/likely pathogenic(P/LP) variants found in 47 individuals, and variants of uncertain significance (VUS) were found in 34.Among couples with adverse pregnancy history: P/LP variants were found in 38 individuals, and VUS were found in 26, for a detection rate of 34.55 %; among members of family history of genetic disease or consanguineous marriages: P/LP variants were found in 9 individuals, and VUS were found in 8, for a detection rate of 50.00 %. Otherwise, we detected 19 ARCs who both carried P/LP variants in the same gene, with a theoretical offspring prevalence of up to 7.42 %.In the absence of probands, carrier screening using WES can provide an efficient tool for screening the molecular etiology of high-risk families.